Dynamics of Bank Credits to Private Sector in the Central and Eastern European Countries - Gergana Mihaylova-Borisova (Finance, Accounting and Business Analysis, 2022)
Objective: The purpose of the research is to analyze credits dynamics, provided by banking sectors in the CEE countries from the international financial crisis to present. Methodology:The study examines the data for domestic credits, provided by banks of the ten Central and Eastern European countries in particular Bulgaria, Romania, Poland, Hungary, Czech Republic, Estonia, Lithuania, Latvia, Slovenia, Slovak Republic. The used methods are descriptive analyses and synthesis. Results: It is found that the bank credits were negatively affected by the observed crises in the last twenties years: international financial crisis, European debt crisis and pandemic crisis. After the COVID-19 crisis the credit growth has started to recover, together with the economies. In 2021, all banking systems in CEE countries reported a recovery of their loan portfolios, recording positive growth rates. However, rising and accelerated inflation since mid-2021 and the subsequent reaction by central banks to curb it faces new challenges forbanks and countries.Implication: The study’s results are important for policy makers, aiming to recover the economic development of countries, as well as to the bank managers, aiming to improve the activity of the managed banking institutions.